A New Insight over Telangiectasia Macularis Eruptiva Perstans - Pinho, André; Cardoso, José Carlos; Oliveira, Hugo; Tellechea, Óscar; Figueiredo, Américo (Journal of the Portuguese Society of Dermatology and Venereology, 2016)
Telangiectasia macularis eruptiva perstans (TMEP) is a rare form of cutaneous mastocytosis with distinctive semiology and histopathology, but that is not free of controversy regarding its individualization as a nosological entity. For some authors, the presence of exclusively telangiectatic macules, along with superficial vascular plexus dilation and low density of mast cell infiltrates in the upper dermis is enough for diagnosis of TMEP. However, some current classifications do not consider this entity separately from other types of cutaneous mastocytosis, because in many cases with telangiectatic lesions, lesions of urticaria pigmentosa can also be observed. We sought to present a case of cutaneous mastocytosis first appearing in the eighth decade of life, with the characteristic clinical, dermoscopic and histopathological findings of TMEP and with no mast cell activation symptoms other than pruritus. However, the complementary workup revealed concurrently the presence of indolent systemic mastocytosis. We additionally revised the most recent evidence favouring the recognition and individualization of this entity.